Effets du stigmate et accès aux soins des femmes prostituées tunisiennes - Faten Msakni (L’Année du Maghreb)
This article aims to highlight the health situation of prostituted women in the city of Sfax. Access to health care is a major problem for them, because of the discrimination and stigma they face on a daily basis, especially on the part of public health officials. Despite the use of the private sector by these women, considered more tolerant with funding, access to care is not without risk. Our work is based on field research on the relationship between clandestine prostitution and health, and interviews with prostituted women, whose practice is formally authorized or clandestine.